Stem cells: to be born great, achieve greatness, or have greatness thrust upon them?. Issue 7 (1st July 2016) - Tran, Raymond; Hoesli, Corinne A.; Moraes, Christopher
Abstract : In this Research Highlight, we describe recent innovations to several aspects of the pluripotent cell therapy pipeline. Abstract : Induced pluripotent stem cells (iPSCs) have opened new doors in providing an ethical, patient-specific cell source towards tissue engineering. Developing these therapies involves the production of reprogrammed iPSCs, expanding them while maintaining pluripotency, then differentiating them into functional tissues. To bring these therapies to the clinic, efficient and GMP-compliant manufacturing methods are required. In this Research Highlight, we describe recent innovations to several aspects of the pluripotent cell therapy pipeline.